Effects of some factors on lipase production by Rhizopus arrhizus - Ozer, D; Elibol, M (Assn Food Scient Techn India, 2000)
Lipase biosynthesis was repressed at high glucose level. The maximum lipolytic activity was recorded at 1 g/l glucose concentration. The inclusion of 1 g/l corn oil in the medium resulted in a 15-fold higher lipase production compared to the control, where no oil was added. Further, it was found that lipase production was highly sensitive to pH changes during fermentation.
Keywords: lipase; Rhizopus arrhizus; lipolytic activity; corn oil